2000
DOI: 10.1128/jvi.74.4.2023-2028.2000
|View full text |Cite
|
Sign up to set email alerts
|

Resistance to Replication of Human Immunodeficiency Virus Challenge in SCID-Hu Mice Engrafted with Peripheral Blood Mononuclear Cells of Nonprogressors Is Mediated by CD8+T Cells and Associated with a Proliferative Response to p24 Antigen

Abstract: High levels of resistance to challenge with human immunodeficiency virus type 1 SF162 were observed in animals engrafted with peripheral blood mononuclear cells of four long-term nonprogressors (LTNPs). Resistance was abrogated by depletion of CD8 ؉ T cells in vivo and was observed only in LTNPs with proliferative responses to p24. In a subgroup of nonprogressors, CD8؉ T cells mediated restriction of challenge viruses, and this response was associated with strong proliferative responses to p24 antigen. Althoug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
18
0

Year Published

2000
2000
2010
2010

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 35 publications
(21 citation statements)
references
References 38 publications
3
18
0
Order By: Relevance
“…35,36 Several factors, both host and virus related, have been implicated in the resistance to disease progression. These include CCR5 37 and CCR5 promoter 38 genotypes, heterozygosity (HLA class I loci), 39 the presence of the HLA B*5701 allele, 40 and CD8 ϩ cytotoxic 41,42 and noncytotoxic cellular immune responses [43][44][45] Besides the known antiviral and adjuvant effects of type I IFN, 17,21,23,24,26,46 these cytokines inhibit HIV infection. [18][19][20]47 In this study, we show that (1) the circulating IPC number and their function are increased in LTSs and (2) LTSs with a high IPC number have significantly lower viral loads than those with a low IPC number (Figures 2,4).…”
Section: Discussionmentioning
confidence: 99%
“…35,36 Several factors, both host and virus related, have been implicated in the resistance to disease progression. These include CCR5 37 and CCR5 promoter 38 genotypes, heterozygosity (HLA class I loci), 39 the presence of the HLA B*5701 allele, 40 and CD8 ϩ cytotoxic 41,42 and noncytotoxic cellular immune responses [43][44][45] Besides the known antiviral and adjuvant effects of type I IFN, 17,21,23,24,26,46 these cytokines inhibit HIV infection. [18][19][20]47 In this study, we show that (1) the circulating IPC number and their function are increased in LTSs and (2) LTSs with a high IPC number have significantly lower viral loads than those with a low IPC number (Figures 2,4).…”
Section: Discussionmentioning
confidence: 99%
“…The quantification of HIV in plasma revealed: (i) that patients enrolled in LTNP cohorts who remained asymptomatic and who maintained high CD4 + T-cell counts were usually those in whom viral load was lowest [6]; and (ii) that, interestingly, some HIV-1-infected individuals consistently maintained undetectable plasma viral loads [2,10,11]. We chose to call these individuals with an undetectable plasma viral load ''HIV controllers'' (HICs) [11], although they are also known as ''elite controllers,'' ''elite suppressors'' [12], or ''elite nonprogressors'' [13].…”
Section: Introducing Hiv Controllersmentioning
confidence: 99%
“…CD8 ϩ T cells from LTNP are very efficient at controlling viral replication in vitro (6,11) and in vivo (16). More recent studies of cytotoxic-T-lymphocyte (CTL) responses in LTNP have shown that, whereas there is no correlation between the frequency of gamma interferonsecreting CD8…”
mentioning
confidence: 97%